Monitoring System Based IOT Of Parking - Marliana Sari; Desman Tumanggor (International Journal of Data Science, Computer Science and Informatics Technology (InJODACSIT), 2021)
Parking problems such as effectiveness, parking efficiency are parking problems that have occurred in manual parking systems. Therefore, it is necessary to have a well-structured parking system capable of offering various solutions to existing parking problems. One solution to building this system is to create a parking monitoring system based on IoT. The Parking System Design aims to design an IOT-based microcontroller that can inform and direct car drivers to an empty parking area and to determine the availability of parking slots, especially in large and multi-storey parking lots.. This design has several common parts that are used, namely NodeMCU ESP8266, IR Obstacle Sensor, LM2596, Servo Motor, Smartphone, Adapter. In this design, the distance on the sensor is less than 5cm, indicating that the parking slot is filled, while the servo motor will control the entrance and exit bars of each vehicle that wants to enter with a delay of 2 seconds. The smartphone will receive data from the sensor to display the number of filled vehicles and empty slots.